Characterization analysis of dynamic behavior of basic ORC under fluctuating heat source. (5th May 2021) - Yu, Xiaoli; Huang, Yan; Li, Zhi; Huang, Rui; Chang, Jinwei; Wang, Lei
Highlights: Dynamic response of a basic ORC system under fluctuating heat source are studied. Amplitude, period and average value of fluctuating heat sources are considered. Effects of characteristics of heat source on safety and efficiency are analyzed. Efficiency and safety are negatively related to fluctuating amplitude and period. Operating rules and maximum allowable fluctuating ranges for basic ORC are obtained. Abstract: Organic Rankine Cycle (ORC) is widely investigated for low-grade waste heat recovery, but its performance deteriorates under heat source with thermal power fluctuations. As the effects of fluctuating heat source on ORC system performance is less investigated, the operating rules of ORC systems under fluctuating heat source are not clear. In this study, the effects of fluctuating amplitude and period for fluctuating heat sources on the performance of a basic ORC system are studied in detail, considering the proposed indicators including safety and efficiency. Afterwards, the allowable fluctuation ranges of heat source are obtained based on requirements of safety and efficiency. Finally, the impact of the average temperature of fluctuating heat sources on the allowable fluctuation range is systematically investigated. The results indicate that the safety limitations and efficiency of the basic ORC system are generally negatively related to fluctuating amplitude and period, and the allowable fluctuation range is generally positively related to average temperature of heat source. To ensure the efficient operation of basic ORC, the allowable relative amplitude is 25–40 K under large fluctuating period while it is higher than 35 K with the fluctuating period smaller than 200 s. This study contributes to provide valuable reference for evaluating the performance of an existing ORC system under different fluctuating heat source conditions.